ndhuh-Undhuh Tradition from the Perspective of Historical Traces of Inculturation of Javanese Culture and Art to Christianity - yuni haryati, christmasela; Suryandoko, Welly (Solah, 2025)
The Undhuh-Undhuh tradition is an annual celebration carried out by Christians more precisely at the Jawi Wetan Christian Church (GKJW) in the village of Mojowarno Jombang. The tradition symbolises the community's gratitude to God for the crops in the form of fruits, vegetables, animal husbandry, and others. The celebration existed and developed into a tradition in 1930 and in 2025 this tradition is 95 years old. However, in reality the Undhuh-undhuh tradition is still not widely known, especially outside the Jombang Regency area. This research not only aims to document and analyse in depth how this tradition is carried out but also to introduce and promote the Undhuh-undhuh tradition to the wider community especially outside Jombang Regency. The problem will be formulated as follows: 1) What is the background of the Undhuh-undhuh tradition. The purpose of this research is to analyse the background and structure of the Undhuh-undhuh tradition at Jawi Wetan Christian Church Mojowarno. This research uses descriptive qualitative research methods. Sources of data obtained in the form of writing from the results of interviews and observations. Data collection techniques are: observation, interviews, photos, videos, and audio recordings. Data analysis techniques through data reduction, data presentation, and conclusion drawing. Data validity using source triangulation and technique triangulation. The results of the research on the background of the Undhuh-undhuh tradition at GKJW Mojowarno are rooted in the life of an agrarian Christian society, where most of its members work as farmers, a form of acculturation between the Javanese harvest tradition and Christian teachings that reflect the integration of local culture and Christian spirituality in the life of the GKJW Mojowarno congregation.